Avaliação do ciclo de vida de polihidroxialcanoatos aplicados como embalagens biodegradáveis - Dela Corte, Guilherme Castro (Universidade Federal de São Carlos, 2025)
This study conducted a life cycle assessment using the openLCA software and the ILCD midpoint+ 2011 and Cumulative Energy Demand methodologies to measure the effect of different biomass generations as carbon sources for the microbial reduction of PHB and PHBV, in a functional unit of 1 ton of polymer resin, and to establish comparisons of ecological indicators against conventional thermoplastics, such as fossil or renewable source HDPE, when molded by designation in a functional unit of 1 500mL capacity bottle. Life Cycle Assessment (LCA) was structured from a cradle-to-gate perspective, considering 4 scenarios with different biomass impact sources for the installation of the PHB and 1 scenario with the carbon source with the lowest environmental impact for the PHBV, and from a cradle-to-grave perspective, considering 8 end-of-life scenarios – industrial aerobic composting or sanitary landfill for the 2 PHA, sanitary landfill or open dump for the 2 HDPE – and 13 midpoint categories – including Water Resource Depletion, Climate Change, Land Use, and Human Toxicity – in accordance with ISO 14040 and 14044. The results indicated that third-generation biomass constituted a more favorable alternative for PHA production in the evaluated indicators. Note that the PHBV had lower environmental performance than the PHB due to the contribution of the propionic acid monomer precursor. PHA bottles had lower environmental impacts than HDPE bottles only in specific scenarios and indicators (Marine Eutrophication, Human Toxicity, Cumulative Non-Renewable Energy Demand), with injection molding and end-of-life identified as the main bottlenecks in the process, whose contributions could be advantageously reduced by adjusting the energy matrix and efficiency gains, sometimes with a more decisive effect than the choice of material itself.
Life cycle assessment of polyhydroxyalkanoates applied in biodegradable packaging
Keywords: Polímeros Biodegradáveis; Polihidroxialcanoatos; Avaliação de Ciclo de Vida; Sustentabilidade; Biodegradable Polymers; Polyhydroalkanoates; Life Cycle Assessment; Sustainability; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis; 13. Ação contra a Mudança Global do Clima